Descriptions of the final instar larvae of seven Chinese Chlorogomphidae species, with taxonomic notes on adults (Odonata: Anisoptera) - Zhang, Haomiao; Tong, Xiaoli (Zootaxa, 2013)
The larvae of seven species of Chlorogomphidae from South Chinaare described based on reared larvae, i.e. Chlorogomphus kitawakii Karube, C. nasutus nasutus Needham, C. papilio Ris, C. shanicus Wilson, C. usudai Ishida, C. yokoii Karube and Chloropetalia soarer Wilson. The adult female of C. kitawakii is first described. Biological information on Chlorogomphidae is provided and a diagnosis of the family proposed.